Bibliometric Analysis of Briquette Research Trends During the Covid-19 Pandemic - Al Husaeni, Dwi Novia (Bumi Publikasi Nusantara, 2022)
This study aims to analyze the scope of research on briquettes using bibliometric analysis and data mapping processes. The research data used is obtained from published journals. The search was conducted using the publish or perish application with the keyword